ETUDE DES DETERMINANTS SOCIOECONOMIQUES DU METIER INFORMEL D’APPRENTI DE GBAKA DANS LA COMMUNE D’ABOBO EN COTE D’IVOIRE - Sinan, Adaman (European Scientific Journal, ESJ, 2015)
In the 80s, the employment situation has become worse in subSaharan Africa in general and particularly in Côte d’Ivoire. This is demonstrated by a reduction in employment in the formal sector due to reform, dissolution and privatization of many state enterprises, executed as part of structural adjustment programs. The consequence of this reduction in employment in the formal or modern sector is the development of the informal sector, particularly in urban areas. The economic capitals which concentrate a large part of the population are most affected by the development of the urban informal sector. The informal sector has grown steadily in Côte d’Ivoire in recent years, occupying a share of more and more important jobs. From 30% in 1998, its share rose to 31% of total employment in 2002. In the urban area of Abidjan, the share of this sector is significantly larger. It therefore occupies, today, the largest share of jobs in Abidjan. It is estimated that the informal economic sector is the second source of employment after agriculture. Also termed as popular economy, the informal economy is a way of life and even survival of the urban population, for which it provides satisfaction for basic needs: food, shelter, clothing, education, healing, moving. It includes a variety of activities (distribution, preparation, restoration), personal services, repair, recovery and especially urban transport). The Informal participates in the process of urbanization, providing jobs and modest remuneration to a flow of new citizens, at the cost of low productivity and quasi stagnant. Therefore, its characteristics are worth well known and this may be achieved through a study of informal production units including the world of urban transport and its traditional dynamic of job promotion.